1798 Ky. Acts 106 - (:unkn) unknown (My University, 1798)
Ch. 54,§ 5: Prohibited "negro, mulatto, or Indian" from possessing or carrying a gun, powder, shot, club, or other weapon or ammunition.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES